2022
DOI: 10.3390/ijerph192013144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Prenatal Alcohol Exposure in Australian Cohort and Cross-Sectional Studies: A Systematic Review of Data Collection Approaches

Abstract: This study sought to determine data collection approaches in Australian cohort studies and explore the potential impact on reported prenatal alcohol exposure (PAE) prevalence and patterns. Inclusion criteria were that studies related to a general Australian antenatal population where PAE was assessed and reported. Studies were excluded if they were not peer reviewed, examined the prevalence of PAE in pregnancies complicated by alcohol-use disorders, or were published in a language other than English. A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 174 publications
0
3
0
Order By: Relevance
“…However, there is no current literature specifically examining Australian psychologists' practices and confidence in assessing PAE, despite addressing and reducing PAE being an important public health issue (Popova et al., 2017). Estimates of PAE prevalence in Australia vary, with a recent systematic review of large Australian cohort studies estimating PAE prevalence in Australia at 48% (Young et al., 2022), whereas data from the National Drug Strategy Household Survey indicates around 35% of women drink alcohol during pregnancy, with 49% of women drinking prior to pregnancy recognition and 25% of women drinking after pregnancy recognition (Australian Institute of Health and Welfare, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no current literature specifically examining Australian psychologists' practices and confidence in assessing PAE, despite addressing and reducing PAE being an important public health issue (Popova et al., 2017). Estimates of PAE prevalence in Australia vary, with a recent systematic review of large Australian cohort studies estimating PAE prevalence in Australia at 48% (Young et al., 2022), whereas data from the National Drug Strategy Household Survey indicates around 35% of women drink alcohol during pregnancy, with 49% of women drinking prior to pregnancy recognition and 25% of women drinking after pregnancy recognition (Australian Institute of Health and Welfare, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of PAE has been calculated at 9.8% (95% CI 8.9, 11.1), with regional variations from 0% in some Middle Eastern countries such as Oman, to 60.4% in Ireland (Popova et al., 2017). A recent meta‐analysis of PAE in Australian cohort studies reported an overall prevalence of 48% (Young et al., 2022). Importantly, 50–60% of women reported alcohol consumption before they become aware of their pregnancy, suggesting PAE is more common in very early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of prenatal ethanol (EtOH) exposure (PEE) varies across the globe. In North‐American countries, 10%–15% of pregnant women reported that they engaged in EtOH use (Popova et al., 2017), but a meta‐analysis that was conducted in Australian samples (Young et al., 2022) indicated a pooled prevalence estimate of 48% (any consumption during pregnancy). Fetal alcohol syndrome is the most severe outcome of PEE.…”
Section: Introductionmentioning
confidence: 99%